Applying a Kano quality model for intelligent green building design strategies in Taiwan - Juan, Yi-Kai; Huang, Sheng-Jhao Hsu; Chen, Hung-Ting (International Journal of Strategic Property Management, 2014)
Intelligent green building (IGB) industry has received considerable global recognition due to the rapid development of advanced technology, intelligent materials, innovative products, and services in recent years. Although various cross-domain experiments and practices with respect to IGB projects are ready for operation, the notion and benefits of IGB are still ambiguous and debatable. The purpose of this study is to apply a Kano quality model and a customer satisfaction matrix to evaluate professional designers’ and general users’ satisfaction, preferences, and acceptability of IGB design strategies. The study result reveals that the proposed approach could be a useful tool to explore similarities and discrepancies of strategy preferences between designers and users, and these findings could effectively decrease the communication gap for future IGB design.First Publish Online: 20 Jun 2014